MODEL OF FORMATION OF DISCUSSIONAL COMPETENCE OF MANAGERS IN THE FIELD OF EDUCATION - Hordiienko, T.; Fu Hong (Видавництво НДУ ім. М. Гоголя, 2024)
The article substantiates the need for and developed a model for the formation of discursive competence of managers in the field of education. Models of formation of discursive competence are not only critically important for the development of education managers themselves, but also have far-reaching consequences for the healthy functioning and continuous improvement of the education system as a whole. Recommendations have been developed to increase the level of formation of the discursive competence of education managers in the management process. The article reveals the following key aspects: the importance of developing communication skills in the modern conditions of education reform; the role of a manager in educational institutions as a communicator who must effectively interact with various stakeholders (teachers, students, parents, authorities, the public); challenges related to managing communication processes in the educational environment, including conflict resolution and public speaking; the concept of "discursive competence" and its components; basic scientific approaches to the formation of discursive competence (linguistic, psychological, sociocultural); the relationship between discursive competence and the professional activity of an educational manager. An overview of the model of formation of discursive competence in management (both generally accepted and specific to the field of education) and the components of the model of formation of discursive competence of educational managers are presented, namely: cognitive component (knowledge of discourse, management communicative strategies); speech component (practical skills of oral and written communication); psychological component (emotional intelligence, conflict management); sociocultural component (ability to adapt communication to different social and cultural conditions), strategic component (planning and adaptation of communication processes depending on the situation). The methods of formation of managers’ discursive competence are presented: the use of interactive learning methods (role-playing games, negotiation simulations, simulation of conflict situations); use of digital technologies for the development of communication skills (webinars, online platforms); implementation of communication development trainings in educational programs for managers of educational institutions.
Keywords: model; discursive competence; criteria and indicators